Հատուկ կարիքներ ունեցող երեխաների ուսուցման և ադապտացման հոգեբանական խնդիրները - Ստեփանյան, Նարինե (Զանգակ հրատ.)
Статья посвящена проблеме обучения и адаптации детей с особыми потребностями. Рассматриваются особенности адаптации и эмоциональной сферы детей, интегрированных в класс, а также психологические факторы, способствующие или препятствующие адаптации и организации обучения детей с особыми потребностями. This article deals with the problems of learning and adaptation of children with the special needs. In the article, we examine the features of adaptation and emotional sphere of children that was integrated into a new class. Similarly, we examine those psychological factors that promote or prevent to adaptation and organization of studies of children with special needs in the premises of inclusive education.
Keywords: Հոգեբանություն